Spatiotemporal changes and driving factors of reference evapotranspiration and crop evapotranspiration for cotton production in China from 1960 to 2019 - Su, Yuexia; Wang, Jian; Li, Junhong; Wang, Lizhi; Wang, Kunfeng; Li, Ao; Gao, Lei; Wang, Zhanbiao (Frontiers in Environmental Science, 2023)
Understanding and tracking changes in crop water requirement is crucial for effective irrigation, water planning, and future decisions. Determining the reference evapotranspiration (ETO) and crop evapotranspiration (ETC) of China cotton is essential for water resource management. This study analyzed the spatiotemporal changes in ETO and ETC at 248 standard stations in cotton production regions of China from 1960 to 2019, and the ETO and ETC of each station were quantified by using the CropWat 8.0 and non-parametric Mann-Kendall test. The impacts of climate change on ETO and ETC were evaluated by analyzing the contribution rate and sensitivity coefficient of climate change. The results revealed distinct distributions of ETO and ETC across various growth stages and spatial scales in the cotton production regions of China. In the Huanghe Valley, the rate of decline for ETO decreased from 787.23 mm to 769.84 mm, while in the Yangtze Valley cotton region, it decreased from 749.19 mm to 735.01 mm. Similarly, in the Northwest inland cotton regions, the rate of decline for ETO reduced from 991.19 mm to 982.70 mm. As for ETC, the rate of decline decreased from 677.62 mm to 654.33 mm in the Huanghe Valley, from 653.02 mm to 625.50 mm in the Yangtze Valley, and from 916.25 mm to 886.74 mm in the Northwest inland cotton regions, respectively.ETO was highly sensitive to maximum air temperature (Tmax), followed by relative humidity (RH), sunshine duration (SD), wind speed at 2 m height (WS) and minimum air temperature (Tmin). WS was the most influential climate variable associated with ETO change, followed by Tmax, SD, RH, and Tmin. Significant declines in WS and SD were indicated in the decrease in ETO in the Huanghe Valley and Yangtze Valley cotton regions. WS allocated a significant decrease in ETO in the northwestern inland cotton region. However, decreased RH and increased temperature commonly reversed the trend of ETO during 2000-2019, and the northwestern inland cotton region had the most significant upward trend. Amidst high temperatures and drought stress, cotton's irrigation needs were rising, posing a significant threat to both cotton production and water resources.